COMPARISON OF CERTAINTY FACTOR AND DEMPSTER SHAFER METHODS INEXPERT SYSTEMS FOR IDENTIFYING FACIAL SKIN TYPES - Dwi Novita; Dadang Haryanto (LKP Tematik Aperta Nusantara, 2026)
Knowledge about health skin face is one of the matter important Because skin face is part outermost from body that often exposed to light sun and dust pollution . One of the factor most important For guard health skin face is with know moreover formerly type skin the face that is owned . Generally face has 5 types skin , namely normal, oily , dry , combination , and sensitive . However , there are still many people have not Can know type skin face alone , so that not seldom they difficult in take action what fits​ For nurse skin his face . So from That objective he did study This is For make A system expert in identify type skin face with method certainty and uncertainty . The results of system expert This expected can help Lots individual For know and understand type skin her face , so that can give more solutions​ appropriate .